Effect of Clay Composition and Human Haircut Waste on Mechanical Properties Mechanical Properties of Epoxy Resin Composites - Darwin Yunus Nasution; Muhammad Delfis (Talenta Publisher, 2024)
The impact of human haircut waste and the nature of clay soil on the mechanical characteristics of epoxy resin composites has been studied. This study utilizes clay sourced from Wonosari Village, Deli Serdang Regency. The clay was pulverized using a pestle and mortar until it reached a smooth consistency. It is then filtered through a 200 mesh screen and subjected to drying in an oven at a temperature of 105â„ƒ for around 3 h until the water content is completely evaporated. Finally, the dried clay stored in a desiccator. The clay powder was subjected to ball milling for 40 h at 350 rpm. The resulting particle size, determined by particle size analysis (PSA), was found at 0.764 Âµm. Next, the human haircut waste obtained from the surrounding campus of Universitas Sumatera Utara was prepared by separating the hair from fine hair and washing it clean. Clay soil powder and human hair cut waste are used as fillers, and some variations of epoxy resin mixtures are used. Morphological SEM analysis shows that clay and human haircut waste can be distributed evenly on epoxy resin composites. Testing of water absorption and mechanical properties of the board based on SNI 01-449-2006 standards include the test of dry bending strength (MoR) and the mode of flexural elasticity (MoE) obtained the optimum composition (50: 50: 1: 1) g against the epoxy resin mixture, waste human haircut, and clay soil obtained the water absorption test results of 1.64% with a value of MoE 36789.03 kgf /cm2 and a value of MoR 664,41 kgf/cm2. Test results of mechanical properties and water absorption have fulfilled the SNI 01-449-2006 quality standards for composite boards.